Bisphenols, Toxic Elements, and Potentially Toxic Elements in Ready-to-Eat Fish and Meat Foods and Their Associated Risks for Human Health - Litrenta, Federica; Nava, Vincenzo; Potortì, Angela Giorgia; Lo Turco, Vincenzo; Sgrò, Benedetta; Di Bella, Giuseppa (Toxics (Basel), 2025)
In this study, simultaneous exposure to bisphenols and toxic and potentially toxic elements from the consumption of ready-to-eat foods was assessed. In total, 120 different ready-to-eat foods purchased in different Sicilian supermarkets and online shops were analysed. BPA was detected in most of the analysed foods. Statistical analysis was performed, differentiating the samples according to geographical origin and packaging type. Good separation between European and non-European samples could be observed, with the former being characterised by lower levels of Cd and Pb, while the latter showed the highest concentrations of Pb and Cd, followed by Mn and Fe. The calculated estimated weekly intake (EWI) was well below the intake levels recommended by regulatory agencies, indicating that ready-to-eat foods can be safely consumed at expected dietary levels. However, the recently established tolerable daily intake (TDI) for BPA increases the risk quotient values to >1, indicating a risk to the consumer.